If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -6 = x + -2 Reorder the terms: -6 + 7x = x + -2 Reorder the terms: -6 + 7x = -2 + x Solving -6 + 7x = -2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -6 + 7x + -1x = -2 + x + -1x Combine like terms: 7x + -1x = 6x -6 + 6x = -2 + x + -1x Combine like terms: x + -1x = 0 -6 + 6x = -2 + 0 -6 + 6x = -2 Add '6' to each side of the equation. -6 + 6 + 6x = -2 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = -2 + 6 6x = -2 + 6 Combine like terms: -2 + 6 = 4 6x = 4 Divide each side by '6'. x = 0.6666666667 Simplifying x = 0.6666666667
| 3x+16=42 | | 3p-1=-2 | | 3(2x-5)+7x=3x+35 | | 3/4x-2 | | -5x^2+4x=91 | | 1.2c+2.6c=4.55 | | 2/7(x-5/4)=-1/7 | | -3(4x+5)=-63 | | 5(x-9)=2(x+7) | | T-6=10 | | H=-16t^2+38t+104 | | 10x=4-(-16) | | 2x-4n=7-n | | ax+bx-9=-10 | | 18xsquared-6x-8= | | 275000.00x=13000.00+25000.00x | | 4/7x=26 | | 2(5x)+3x=7 | | 3(x+8)=x+12 | | 2x-4n=18-n | | -3y-5(y+4)=4 | | 7/3x-5 | | 2(9-2x)=26 | | 24x+12=63 | | 143=11S+11 | | B=17-14 | | 12-9x=4-5x | | 2x-2x=9 | | 4B-3=5(B-9) | | -2x-1=s | | B=14-14 | | 3(k-5)-2(k+1)-13=-24 |